Penerapan Model Problem Based Learning pada Materi Jaring-Jaring Kubus dan Balok di Kelas V SD Plus Bakti Nusantara 666 - Dita Dinar Rafidah; Marcella Nurul Annisa; Ossie Destiani Fadhilah; Komariah Komariah (Journal on Education, 2023)
Learning mathematics in elementary school is very important to improve students' thinking patterns. Selection of learning models, learning strategies, and making learning media must be in accordance with the character of students. This research was conducted by the writer at SD Plus Bakti Nusantara 666 using a qualitative approach research method in the form of a case study. The learning model used is by applying the Problem Based Learning Model which aims to enable students to think critically about a problem. The material being taught is about cube nets and beam nets in class V SD. Which is where students are taught to distinguish between cube nets and beam nets, and students are asked to make, shape, and be able to distinguish block nets and cube nets. Student learning outcomes were quite satisfactory. The average student gets a score of 90. The purpose of this research is to find out how influential the Problem Based Learning Model is taught in the material of cube nets and beam nets.